2016
DOI: 10.1021/acs.jpcc.6b01819
|View full text |Cite
|
Sign up to set email alerts
|

Electrolytes at the Hydroxylated (0001) α-Quartz/Water Interface: Location and Structural Effects on Interfacial Silanols by DFT-Based MD

Abstract: Structural properties of NaCl, KCl, and NaI electrolytes forming an electrical double layer (EDL) at the fully hydroxylated (0001) α-quartz/liquid water interface have been investigated by means of first-principles molecular dynamics simulations (FPMD). Cations are found in inner-sphere conformations, directly bonded on two in-plane silanol groups that replace water molecules that would be present in the first solvation shell of the aqueous cations. Anions are located within the second/third water layer above … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
56
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 50 publications
4
56
3
Order By: Relevance
“…34,[70][71][72][73] The HB lengths at a neat water/ silica interface and electrolyte/silica interfaces were calculated and 7 days, pH7 2046 days, pH7 7 days, pH9 2046 days, pH9 the results showed that the intra-surface HB between silanol and silanol is weakened significantly when electrolytes are present at the interface. 73 This study also showed that the perturbing effect of cation adsorption on interfacial properties is stronger than that of anion adsorption. 71 The acidity of surface silanol groups varies with the type of electrolyte present at the interface.…”
Section: Simulations Of Hydrogen Bonds In Nano-porous Silica Gelsmentioning
confidence: 99%
“…34,[70][71][72][73] The HB lengths at a neat water/ silica interface and electrolyte/silica interfaces were calculated and 7 days, pH7 2046 days, pH7 7 days, pH9 2046 days, pH9 the results showed that the intra-surface HB between silanol and silanol is weakened significantly when electrolytes are present at the interface. 73 This study also showed that the perturbing effect of cation adsorption on interfacial properties is stronger than that of anion adsorption. 71 The acidity of surface silanol groups varies with the type of electrolyte present at the interface.…”
Section: Simulations Of Hydrogen Bonds In Nano-porous Silica Gelsmentioning
confidence: 99%
“…Recent AIMD simulations of deprotonated silica surfaces 27,35 have reported persistent Na + coordination to the quartz (001) surface for the duration of trajectory lengths of ∼10 ps.…”
mentioning
confidence: 99%
“…Ab initio molecular dynamics (AIMD) has been used to explore the structure and dynamics of water-oxide interfaces [144][145][146][147][148][149][150][151][152][153][154][155][156][157][158][159]. In particular, AIMD can be used to compute vibrational spectra and non-linear optical response [147,[160][161][162][163][164], and as such is a key tool to help interpret experimental observations.…”
Section: Latest Developments In Molecular Modelingmentioning
confidence: 99%